Meiotic chromosome dynamics and double strand break formation in reptiles - Marín-Gual, Laia; González-Rodelas, Laura; M. Garcias, Maria; Kratochvíl, Lukáš; Valenzuela, Nicole; Georges, Arthur; Waters, Paul D.; Ruiz-Herrera, Aurora (Frontiers in Cell and Developmental Biology, 2022)
During meiotic prophase I, tightly regulated processes take place, from pairing and synapsis of homologous chromosomes to recombination, which are essential for the generation of genetically variable haploid gametes. These processes have canonical meiotic features conserved across different phylogenetic groups. However, the dynamics of meiotic prophase I in non-mammalian vertebrates are poorly known. Here, we compare four species from Sauropsida to understand the regulation of meiotic prophase I in reptiles: the Australian central bearded dragon (Pogona vitticeps), two geckos (Paroedura picta and Coleonyx variegatus) and the painted turtle (Chrysemys picta). We first performed a histological characterization of the spermatogenesis process in both the bearded dragon and the painted turtle. We then analyzed prophase I dynamics, including chromosome pairing, synapsis and the formation of double strand breaks (DSBs). We show that meiosis progression is highly conserved in reptiles with telomeres clustering forming the bouquet, which we propose promotes homologous pairing and synapsis, along with facilitating the early pairing of micro-chromosomes during prophase I (i.e., early zygotene). Moreover, we detected low levels of meiotic DSB formation in all taxa. Our results provide new insights into reptile meiosis.